Interpol's strategy in enhancing the regional network to combat human trafficking in West Africa - Sayuti, Aliah Lestari; Rofii, Muhammad Syaroni; Salya, Sundawan (International Journal Labs, 2023)
The main problem in this study is the human trafficking practices in West Africa. Trafficking in human beings is a serious transnational crime involving blackmail, exploitation, and forced labor. Victims of human trafficking are often forced to work in modern slave industries, such as prostitution, agriculture, and manufacturing. They can also experience physical and psychological violence. Human trafficking has many root causes, including poverty, gender inequality, and conflict. Research methods use qualitative descriptive approaches with data analysis techniques that focus on understanding a problem, context, complexity, and subjectivity to more detail about the data source. Results: Interpol's role and initiatives have saved hundreds of victims of human trafficking in West Africa. The organization has been a valuable partner for governments and law enforcement agencies in the region in combating human trafficking crimes and rescuing victims. Interpol's efforts to rescue victims of human trafficking in West Africa are critical to combating this crime. By raising awareness, identifying victims, disrupting trafficking networks, and providing support to victims. Interpol recognizes the urgent need to facilitate interstate police cooperation in addressing transnational crime, regional security and resilience.